(untitled) (Journal of Sciences & Technology, 2019)
The effect of bulk parameters (¬diffusion length (Ln), absorption coefficient (α) and acceptor concentration (Na)) on the cathodoluminescence intensity (ICl) of p type CdTe has been theoretically investigated. To do this a self-consistent calculation method of (ICl) has been used. The obtained results show that ICl decreases when Ln and α increase up to a certain excitation energy E0, and then begins to decrease. The maximum of the ICl = f(E0) curves shifts towards high energies.